OPTIMIZATION OF MSMEs BASED TOURISM VILLAGES THROUGH THE LOCAL BRANDING TOWARDS SUSTAINABLE OF TOURISM PULO PANJANG VILLAGE SERANG - Afiah, Efi Tajuroh; Munawaroh, Munawaroh; Zulfikar, Meiby; Suhandi, Suhandi (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research activity aims to explore and develop the potential of MSME-based tourism villages through local branding. This development is one of the efforts to drive the community's economy, where the MSMEs in Pulo Panjang Village have not been able to be developed optimally. The local branding design was carried out in Pulo Panjang Village, which has many MSMEs and tourist attractions with excellent development potential. The research method uses qualitative methods through observation, interviews, Forum Group Discussion (FGD), and documentation presented as data. This research shows that developing MSME-based tourism villages with local branding must apply the Penta helix method. There must be a collaboration with several parties, such as the government, entrepreneurs, local media, academics, and the community in Pulo Panjang Village